Limited resources or limited luck? Why people perceive an illusory negative correlation between the outcomes of choice options despite unequivocal evidence for independence - Déborah Marciano; Eden Krispin; Sacha Bourgeois-Gironde; Leon Y. Deouell (Judgment and Decision Making, 2019)
When people learn of the outcome of an option they did not choose (the alternative outcome) before they know their own outcome, they see an illusory negative correlation between the two outcomes, the Alternative Omen Effect (ALOE). Why does this happen? Here, we tested several alternative explanations and conclude that the ALOE may derive from a pervasive belief that good luck is a limited resource. In Experiment 1, we show that the ALOE is due to people seeing a good alternative outcome as a bad sign regarding their outcome, relative to seeing a neutral alternative, but find no evidence for seeing a bad alternative outcome as a good sign. Experiment 2 confirms that the ALOE replicates across tasks, and that the ALOE cannot be explained by preconceptions regarding outcome distribution, including: 1) the Limited Good Hypothesis (zero-sum bias), according to which people see the world as a zero-sum game, and assume that resources there means fewer resources here, and/or 2) a more specific assumption that laboratory tasks are programmed as zero-sum games. To neutralize these potential beliefs, participants had to draw actual colored beads from two real, distinct bags. The results of Experiment 3 were consistent with a prediction of the Limited Luck Hypothesis: by eliminating the value of the outcomes we eliminated the ALOE. Taken together, our results show that either the limited good belief is so robust that it defies strong situational evidence, or that individuals perceive good luck itself as a limited resource. Such a limited-luck belief might have important consequences in decision making and negotiations.